Artificial intelligence in higher education: student perspectives on practices, challenges, and policies in a transitional context - Çerkini, Bashkim; Bajraktari, Kaltrina; Çibukçiu, Blerina; Ramadani, Fehmi; Zejnullahu, Fakije; Hajdini, Lulzim (Frontiers in Education, 2025)
This study explores the integration of Artificial Intelligence (AI) in higher education, with a particular focus on Kosovo’s transitional educational system. It investigates the students’ perceptions, the challenges they encounter, and institutional policies related to the AI use in learning practices. This research employed a mixed-methods design, including both quantitative and qualitative data. The qualitative data were assessed through thematic analysis, while quantitative data were processed using Statistical Method using SPSS. A questionnaire was designed based on SATAI (Student Attitudes Toward Artificial Intelligence) and Student Perspectives on AI in Higher Education: Student Survey, to gain insights into students’ perspectives. A total of 554 students participated from public and private universities in Kosovo. The results indicated a significant positive correlation between AI and positive students’ attitudes (r = 0.813, p < 0.001)–students who used AI often tended to view it positively and use it more. Conversely, students who lacked AI training and experience reported significant challenges in use. Furthermore, the findings revealed that positive perceptions of institutional policies are associated with increased AI use (B = 0.13, p < 0.001). However, gender and age differences didn’t have a significant influence on attitudes and the use of AI. The overall results highlight the critical need to construct clear policies, comprehensive and effective training to maximize the benefits of AI in the academic context.